The Role of Talent Management in the Relationships between Employee Engagement: A Study of GLCs - Aizat Ramli A.; Isa A.; Baharin N.L.; Izwar Ibrahim H. (EDP Sciences, 2023)
Competition; Least squares approximations; Data collection; Employee engagement; Partial least square (PLS); Talent management; Value creation; Human resource management